Analiza zróżnicowania regionalnej przestrzeni Unii Europejskiej ze względu na innowacyjność sektorowej struktury zatrudnienia - Strahl, Danuta; Markowska, Małgorzata (The Analysis of European Union Regional Space Diversification Related to Innovativeness of Sectoral Employment Structure, 2006)
The article presents an analysis of the European, regional space diversification related to employment structure innovativeness. Indicators reflecting the share of the employed in market and non-market services and the level of GDP per capita in PPS were used to illustrate the employment structure innovativeness. The analysis was performed at the national level, for 25 European Union countries, as well as at the regional level, for 250 NUTS-2 type regions. There were also used such descriptive statistics as: the mean value, standard deviation, variability coefficient or range in order to describe the level of European, regional space diversification. The performed studies facilitated establishing the degree of span in the field of economy innovativeness between regions of each country as well as among the EU countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 75-85